Sistem Informasi Reservasi dan Pembayaran Cicilan Ortodonti Berbasis Website dengan Tracking Pasien - Ayu Sekar Ningrum; Meme Susilowati (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2026)
This research focuses on developing an information system for orthodontic treatment reservations and installment payments to address manual operational challenges at partner dental clinics. Currently, conventional scheduling and financial recording processes often lead to schedule conflicts, risks of overdue receivables, and a lack of medical progress transparency for patients. Using the Three Major Phases framework development method, this system is designed to integrate dynamic reservation management, phased payment schemes with automatic notifications, and structured patient medical progress tracking features. The system was built using the PHP programming language and MySQL database. The development of this system aims to enhance clinic operational efficiency and provide easy information access for patients to monitor their orthodontic treatment progress in real-time. Through the implementation of a website-based system, it is expected that clinic administrative processes can be better digitized to improve service quality and patient satisfaction.